Virome Profiling, New Virus Identification and the Prevalence and Distribution of Viruses Infecting Chieh-Qua (Benincasa hispida Cogn. var. chieh-qua How) in China - Haiyan Che; Yuxin Ma; Yating Lin; Tuizi Feng; Daquan Luo; Haibo Long (Viruses, 2023)
The cucurbit vegetable chieh-qua (Benincasa hispida var. chieh-qua How) is an important crop in South China and southeast Asian countries. Viral diseases cause substantial loss of chieh-qua yield. To identify the viruses that affect chieh-qua in China, ribosomal RNA-depleted total RNA sequencing was performed using chieh-qua leaf samples with typical viral symptoms. The virome of chieh-qua comprises four known viruses (melon yellow spot virus (MYSV), cucurbit chlorotic yellows virus (CCYV), papaya ringspot virus (PRSV) and watermelon silver mottle virus (WSMoV) and two novel viruses: cucurbit chlorotic virus (CuCV) in the genus Crinivirus and chieh-qua endornavirus (CqEV) in the genus Alphaendornavirus. The complete genomes of the two novel viruses in chieh-qua and three other isolates of CuCV in pumpkin, watermelon and cucumber were determined and the recombination signals of pumpkin and watermelon isolates of CuCV were detected. A reverse transcriptase PCR indicated that the dominant viruses of chieh-qua in Hainan are MYSV (66.67%) and CCYV (55.56%), followed by CuCV (27.41%), WSMoV (7.41%), cucumber mosaic virus (8.15%), zucchini yellow mosaic virus (6.67%), PRSV (6.67%) and CqEV (35.56%). Our findings support diagnostic and prevalence studies of viruses infecting chieh-qua in China, enabling sustainable control strategies for cucurbit viruses worldwide.